2016
DOI: 10.1002/jrs.4935
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disulfide bonds on protein folding, unfolding, and misfolding investigated by FT–Raman spectroscopy

Abstract: Disulfide bond is relevant to many protein folding/unfolding functions and conformational diseases. To elucidate the effects of disulfide bonds on protein folding, unfolding, and misfolding, we performed Fourier transform-Raman measurements on serial chemical-induced denaturations of bovine serum albumin (BSA). By directly monitoring Raman stretching at S-S (~507 cm À1 ), S-H (~2566cm À1 ), amide I (1655 cm À1 for α-helix; 1667 cm À1 for β-sheet structure), and amide III (>1300 cm À1 for α-helix; 1246 cm À1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
0
28
1
2
Order By: Relevance
“…Processing treatments such as salting or cooking all assist in the changes of secondary and tertiary structure of proteins. Determining the structures of various proteins would aid in our understanding of the mechanisms of protein functions and of the changes of proteins digestibility (Wang, Huang, Lin, & Chen, 2016). Disulfide bonds stabilize the tertiary structure of proteins; 500-550 cm −1 are usually assigned to the S-S stretching vibrations of disulfide bonds, which are formed between the cystine of proteins (Brandt et al, 2008).…”
Section: Evaluating Protein Tertiary Structure By the Normalized Intementioning
confidence: 99%
See 1 more Smart Citation
“…Processing treatments such as salting or cooking all assist in the changes of secondary and tertiary structure of proteins. Determining the structures of various proteins would aid in our understanding of the mechanisms of protein functions and of the changes of proteins digestibility (Wang, Huang, Lin, & Chen, 2016). Disulfide bonds stabilize the tertiary structure of proteins; 500-550 cm −1 are usually assigned to the S-S stretching vibrations of disulfide bonds, which are formed between the cystine of proteins (Brandt et al, 2008).…”
Section: Evaluating Protein Tertiary Structure By the Normalized Intementioning
confidence: 99%
“…Disulfide bonds stabilize the tertiary structure of proteins; 500-550 cm −1 are usually assigned to the S-S stretching vibrations of disulfide bonds, which are formed between the cystine of proteins (Brandt et al, 2008). Band located at 530 cm −1 has been assigned to disulfide bonds in the gauche-gauche-trans (Wang et al, 2016). Interestingly, the intensity of S-S at 530 cm −1 significantly decreased from the raw to 120°C, which could be explained that cooking temperatures caused the transformation from gauche-gauche-trans conformation to all-gauche and trans- Figure 3.…”
Section: Evaluating Protein Tertiary Structure By the Normalized Intementioning
confidence: 99%
“…The fitted peak areas of Raman spectroscopy at 500–510 cm −1 , 516–530 cm −1 and 535–545 cm −1 were used to indicate the content of gauche‐gauche‐gauche (g‐g‐g), trans‐gauche‐gauche (t‐g‐g) and trans‐gauche‐trans (t‐g‐t) conformations of disulfide bonds . The percentage of each peak area to the total peak area was used to indicate the percentage of each conformation, and is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The fitted peak areas of Raman spectroscopy at 500-510 cm −1 , 516-530 cm −1 and 535-545 cm −1 were used to indicate the content of gauche-gauche-gauche (g-g-g), trans-gauche-gauche (t-g-g) and trans-gauche-trans (t-g-t) conformations of disulfide bonds. 20,36 The percentage of each peak area to the total peak area was used to indicate the percentage of each conformation, and is shown in Table 2. The percentage of g-g-g and t-g-t conformations of disulfide bond decreased significantly (P < 0.05) as the HSH speed increased, whereas the t-g-g conformation significantly increased.…”
Section: Tertiary and Quaternary Structurementioning
confidence: 99%
“…They found that both disulfide bonds and secondary structure (mostly in α‐helix) of BSA appeared relatively stable even when the protein was unfolded by urea solution. However, disulfide bonds were completely reduced, and protein secondary structure changed from α‐helix to a relatively β‐sheet dominant structure when the protein was modified by the mixed solution of urea and dithiothreitol (urea/DTT) …”
Section: Biosciencesmentioning
confidence: 99%